Moçambicanidade sob frestas: negociação e subversão nos romances de Ungulani Ba Ka Khosa e Mia Couto - Silva, Thiago Wesley Oliveira Custódio (2021)
The research sources covered in this dissertation are two historical novels, by two Mozambican writers, Ungulani Ba Ka Khosa and Mia Couto. From the first, we will analyze the narratives Ualalapi and The women of the emperor, published respectively in 1987 and 2018, composing a single work. And from the second, the trilogy Sands of the emperor (Women of the ashes, The sword and the spear and The drinker of horizons), published respectively in 2015, 2016 and 2017. The narratives are inspired by the same historical matrix: the end of the Empire of Gaza, in southern Mozambique, ruled by Emperor Ngungunhane, after losing the war to the Portuguese. With these sources, the research prefigures the problem of understanding how the representations of power relations are presented in these narratives and how they produce discourses that subvert and confront the Mozambicanity forged by the power established the post-independence period, in 1975. The central objective, thus, is to analyze the internal discourses of these narratives, focusing on the representations of the multiple power relations crossed by Portuguese colonialism, by the political, social and cultural structures of the African peoples and their relationship, when we look at the political conjuncture at the time of production narratives, with Mozambicanity and its imaginary. It is by the light of theorists like Stuart Hall, Achille Mbembe, Michel Foucault, Francisco Noa, Homi Bhabha, Thomaz Tadeu da Silva, among others that we will debate concepts such as identity, negotiation, hybridism, representation, power relations, which will be fundamental to reflect on the particularities of Mozambican literature and its relation with the constitution of Mozambicanity